THE TRANSLATION OF EUPHEMISTIC EXPRESSIONS IN TEMPO.CO ONLINE NEWS TEXT - Deviyanti, Revinia; Rasyid, Yumna; Nuruddin, Nuruddin (STKIP Siliwangi, 2020)
Euphemism is the use of good expressions. It can be found in a variety of texts, especially in news texts. News texts are read by various groups of people. Therefore, the choice of proper words used by the writers is necessary. This is a qualitative research using content analysis method. This research examines the types of euphemistic expressions and the translation techniques found in 20 Tempo.co news texts, both in Indonesian and their translation in English. The theory of Allan and Burridge is used to classify the types of euphemistic expressions. There are 46 euphemistic expressions found in Tempo.co online news texts which are classified into 9 types of euphemism such as figurative expression, jargon, circumlocution, general for specific, part of whole euphemism, remodelling, omission, colloquial, and one for one substitution. The euphemistic expressions are translated using 4 translation techniques. They are generalization, borrowing, transposition, and literal translation.Keywords: euphemism, types of euphemism, translation techniquesÂ Â